Observational constraints on f(R, T) gravity with $$f(R,T) = R + h(T)$$ f ( R , T ) = R + h ( T ) - Gopal Sardar; Akash Bose; Subenoy Chakraborty (European Physical Journal C: Particles and Fields, 2023)
Abstract The present cosmological model deals with modified f(R, T) gravity theory with $$f(R,T)=R+h(T)$$ f ( R , T ) = R + h ( T ) in the background of homogeneous and isotropic FLRW space-time model. Four choices of h(T) have been studied and examined from two observational data sets. It is found that model III, namely, the linear combination of power law and logarithmic form is more consistent with observed data than the others. However, all four considered models are a worse fit than the LCDM model.